2015
DOI: 10.1007/s10067-015-2896-z
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors associated with functional disability in outpatients with rheumatoid arthritis in Southwest China

Abstract: With the rising number of patients with rheumatoid arthritis (RA), there is a limited understanding about sociodemographic factors that influence functional disability in Chinese patients. In order to provide more targeted interventions to improve health-related quality of life (HRQoL) for patients with RA, we conducted a cross-sectional study to investigate the level and influencing factors of functional disability. Convenient samples were collected in outpatients with RA from a rheumatological center in sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 31 publications
2
24
1
1
Order By: Relevance
“…One possible explanation for the different results was the existence of cultural diversity and the different participants included in different studies with either Chinese or Western cohorts. Not surprisingly, disease duration was significantly associated with functional disability in Chinese patients with RA, which was in line with previous studies [11, 12]. When RA progresses, the joints were increasingly affected, which possibly increased the HAQ-DI score.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…One possible explanation for the different results was the existence of cultural diversity and the different participants included in different studies with either Chinese or Western cohorts. Not surprisingly, disease duration was significantly associated with functional disability in Chinese patients with RA, which was in line with previous studies [11, 12]. When RA progresses, the joints were increasingly affected, which possibly increased the HAQ-DI score.…”
Section: Discussionsupporting
confidence: 90%
“…It could be explained by some cultural features which may influence disease management in China. Previous studies have reported that gender [10], age [11, 16], SES [12], comorbidities [13, 14], and pinch strength [17, 20] were associated with the HAQ-DI in RA patients. However, our study demonstrated there were no association between these variables and the HAQ-DI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important reason for the discrepancy in the MCS comparisons may be that considerable developments in treatment in recent years have had a significant beneficial effect on RA patients’ HRQOL [39]. However, for the discrepancy in the PCS comparisons, the disease can become very severe and difficult to control by the time rheumatological care is accessed due to limited knowledge or self-management about RA in mainland China [40]. Other reasons may be some differences in the sources and cultural backgrounds of subjects, and the interpretation of the concept of HRQOL across studies.…”
Section: Discussionmentioning
confidence: 99%
“…La AR afecta aproximadamente al 1% de la población mundial, y a medida que avanza la enfermedad, las consecuencias para la salud del paciente se identifican por la pérdida de la movilidad articular, deformidad, discapacidad, dolor crónico y la presencia de emociones negativas como la ansiedad, la depresión, el estrés y la desesperanza (Gibofsky, 2012;Santiago, Geenen, Jacobs & Da Silva, 2015;Zhao, Chen & Chen, 2015), además de presentar dependencia física y emocional, fatiga, rigidez matutina y trastornos del sueño, entre otros (Purabdollah, Lakdizaji, Rahmani, Hajaliu & Anzarin, 2015).…”
Section: Introductionunclassified